An Assessment of National EMT Certification Among Enlisted Military Medics. (1st March 2017) - Harper, Stephen; Crowe, Remle; Bentley, Melissa; Kharod, Chetan; Walrath, Benjamin
ABSTRACT: Background: Navy Hospital Corpsmen (HMs) are the Navy equivalent to Emergency Medical Technicians (EMTs) both in-garrison and on the battlefield. In 2000, the Emergency Medical Services (EMS) Education Agenda for the Future highlighted the need for a single certification agency to provide consistent evaluation of entry level competence for each nationally recognized EMS provider level. Administered by the National Registry of EMTs (NREMT), National EMT Certification is currently utilized by 46 states, the District of Columbia, four territories, and six federal organizations as part of their processes for granting licensure. Unlike the Air Force (USAF) and Army (USA), the Navy (USN) does not require National EMT Certification to perform the duties equivalent to a civilian EMT. Our objective is to describe the number of USN HMs, USAF medics, and USA combat medics who have obtained National EMT Certification from 2007 through 2014. Methods: Results from all USN HMs, USAF medics, and USA combat medics who tested between January 1, 2007 and December 31, 2014 were queried from the NREMT database. Descriptive statistics were calculated based on a retrospective review of prospectively collected testing data. Results: During the study period, 89, 136 Military Service Members received their EMT certification from the NREMT. The breakdown of the total and percent of total is; USA Combat Medics ( n = 69, 761; 78.3%), USAF Medics ( n = 16, 195; 18.1%), and USN HMs ( n = 3, 180; 3.6%). Approximately 4, 000 HMs graduate yearly from the Department of Defense Medical Education and Training Campus at Fort Sam Houston, Texas and 253 HMs obtained certification in 2014. Conclusions: About 6.3% (253/4, 000) HMs obtained National EMT Certification in 2014, which is a nationally recognized standard for entry-level competence utilized by civilian EMTs and other branches of the military. More information about those HMs that obtain certification may help Commanders maximize the number of HMs obtaining certification. Mandating National EMT Certification for HMs graduating from initial entry training would increase the numbers obtaining certification and bring them in line with USA, USAF, and national movement toward requiring certification for medical providers at all levels.